IMPLEMENTASI PENDIDIKAN INKLUSIF DI KOTA TASIKMALAYA (STUDI KASUS: SDN GUNUNG LIPUNG 4 KOTA TASIKMALAYA) - Puji Imam Muttaqien (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
This research aims to determine how the success or failure of implementation of the education policy inclusive in Tasikmalaya city based on the regulation of Tasikmalaya Mayor Number 46 year 2014 about the implementation of inclusive education in Tasikmalaya City. The problems that arise include facilities and infrastructures that still lack support of the inclusive education process, funding sources for the course of inclusive education programs and human Resources Special escort teachers (GPK) that are still lacking and need additions. In research is an analytical descriptive study by using data collection techniques such as observation of the research object in a manner of frankly and later subsequent interview techniques on informant relevant to this study and documentation studies. For the data analysis techniques in this research is conducted through three activities that occur simultaneously namely data reduction, data presentation, and withdrawal of conclusions or verification. As for the analysis of data on this research use triangulation techniques. Based on the results of research in SD Negeri 4 Mount Lipung consistently and sustainably enough to run an inclusive education program. But there are still some issues that arise such as communication that lacks details between the education office as a policy maker and the school as an impelentor or policy executor. Still need special attention from the Government related to human resources special Companion teachers (GPK), facilities and infrastructure resources that support inclusive education programs and also special funding sources for inclusive education programs. But SD Negeri 4 mount Lipung can be categorized successfully in the implementation of the inclusive education program policy.